Climatic control on eastern Andean denudation rates (Central Cordillera from Ecuador to Bolivia) - Pepin, E. (2013)
The suspended sediment yield and associated current denudation rates of eight large catchments located along the eastern range of the central Andes have been determined. The catchments have been chosen as mountainous and mainly denudational basins to avoid sediment sinks that could bias our analysis. Discharge data and suspended sediment concentrations measured at each catchment outlet have been combined to produce average annual sediment fluxes and thus yields and current denudation rates over time spans of 2–43 years. Denudation rates range between 0.25 and 1.20 mm yr−1 with a north to south gradient. Maximum values are observed in Bolivian catchments. A correlation analysis has been carried out to determine the main controlling factors of current denudation rates at the catchments spatial scale. Climatic, topographic and lithologic parameters have been studied. Our results suggest that denudation rate is mainly controlled by the climate and especially its variability. A strong negative correlation between mean average runoff and denudation rate is detectable whereas topography and lithology are playing no significant role. A multiple regression analysis is suggesting that large Andean catchment denudation rate could be efficiently estimated by the variability of the climate. Combining both slope and lithologic secondary parameters improves the estimation. Finally, the important effect of climate variability on erosion and sediment transport seems to be enhanced by the potential protection of the vegetation cover that is directly controlled by the climate regime.